Application of Synergistic Phenomena for Enhanced Production of Alpha 1,4 D- Glucan Glucanohydrolase Using Submerged Fermentation: Alpha 1, 4 D- glucan glucanohydrolase production - Abdullah, Roheena; Cheema, Javeria Saleem; Aftab, Mahwish; Kaleem, Afshan; Iqtedar, Mehwish; Saleem, Faiza; Iftikhar, Tehreema (Cellular and Molecular Biology, 2022)
The study revealed enhanced production of α 1, 4 D glucan glucanohydrolase utilizing the synergistic phenomena of bacterial hetero-culture. For this purpose, 101 hetero-cultures were screened qualitatively and quantitatively. The bacterial hetero-culture showing the highest amylolytic potential was identified as Bacillus subtilis and Bacillus amyloliquefeciens by 16S rDNA sequencing technique. Different fermentation media were evaluated and M 5 gave maximum GGH production. Different physicochemical parameters like incubation time, temperature, initial pH and inoculum size was optimized. The optimal enzyme production was obtained at 24 h, 37oC, pH 7.0 and 3% inoculum size. Glucose (3%), ammonium sulphate (1.5%) and yeast extract (2.0%) was selected as best carbon and nitrogen source, respectively. The novelty of the present piece of research was the application of the hetero-culture technique for enhanced GGH production using submerged fermentation which was not experienced before with these strains.